2018
DOI: 10.2754/avb201887020115
|View full text |Cite
|
Sign up to set email alerts
|

The effect of post-calving pain management with carprofen on stress, reproduction, and milk yield in cattle

Abstract: Previous research has shown that the administration of non-steroidal anti-inflammatory drugs in postpartum cattle has the potential to be a viable way to improve productivity and reproduction, although further research is necessary to optimise recommendations for producers. The aim of this research was to determine the influence of carprofen on dairy cows using a number of different indices including stress, reproduction, and milk yield data. The experiment was carried out on 100 first-lactation dairy cows. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
3
1
Order By: Relevance
“…These results are in agreement with other studies that have evaluated reproductive performance after NSAID administration (Carpenter et al 2016;Meier et al 2014;Richards et al 2009). In contrast, our results differ with the findings by Antanaitis et al (2018) and Giammarco et al (2018) that report an 8.5% increase of pregnancy rate and a 25% increase of the pregnancy rate to first service after NSAID administration. These contradictory results could be explained by the estrus synchronization protocol regularly used in this farm.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These results are in agreement with other studies that have evaluated reproductive performance after NSAID administration (Carpenter et al 2016;Meier et al 2014;Richards et al 2009). In contrast, our results differ with the findings by Antanaitis et al (2018) and Giammarco et al (2018) that report an 8.5% increase of pregnancy rate and a 25% increase of the pregnancy rate to first service after NSAID administration. These contradictory results could be explained by the estrus synchronization protocol regularly used in this farm.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, only few studies have reported an improvement in health and longevity after administration of NSAID in the early postpartum. Recently, Antanaitis et al (2018) observed a decrease in the incidence of retained placenta (66.7%), puerperal metritis (66.7%) and clinical mastitis (100%) in primiparous cows treated with a single dose of carprofen. Similarly, Shock et al (2018) and Giammarco et al (2018) reported a decrease in the risk of early culling after the administration of meloxicam or either carprofen/flunixin meglumine, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…While medication of healthy animals is difficult to justify, there is mounting evidence that parturition is painful in cattle [26,27]. The use of NSAID products in cows following calving has promoted greater intakes [28], alterations in activity level [10], higher milk production [29,30], lower somatic cell counts [26], and culling rates [30] in immediate post-partum period. Given the increased public scrutiny faced by the industry over issues of animal welfare [31], there may come a time when pain control is given to every cow following parturition.…”
Section: Resultsmentioning
confidence: 99%
“…Post-parturition inflammation and pain is ameliorated through the administration of an NSAID in the hours after birth (e.g. meloxicam or carprofen), resulting in increased feed intake, milk production and subsequent reproduction, while reducing mastitis, metritis and voluntary culling in barn-housed cows and heifers (Stilwell et al 2014;Antanaitis et al 2018;Shock et al 2018). There are few data on the prevalence of pain mitigation strategies for dystocia in dairy cattle.…”
Section: Transition To the Milking Herdmentioning
confidence: 99%